2018
DOI: 10.3389/fgene.2018.00513
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-Dependent Upregulation of Adcyap1r1 Expression in Nucleus Accumbens Is Associated With Genetic Predisposition of Sex-Specific QTL for Alcohol Consumption on Rat Chromosome 4

Abstract: Humans show sex differences related to alcohol use disorders (AUD). Animal model research has the potential to provide important insight into how sex differences affect alcohol consumption, particularly because female animals frequently drink more than males. In previous work, inbred strains of the selectively bred alcohol-preferring (P) and non-preferring (NP) rat lines revealed a highly significant quantitative trait locus (QTL) on rat chromosome 4, with a logarithm of the odds score of 9.2 for alcohol consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 68 publications
1
9
0
Order By: Relevance
“…Our present study also demonstrates that this postsynaptic effect of PACAP in POMC neurons is sexually differentiated; with females being more sensitive than males in the presence of E 2 . This is consistent with the findings of Spence et al [57], in which expression of the Adcy-ap1r1 gene, encoding the PAC1 receptor, is upregulated in the nucleus accumbens of females compared to males, and enhanced by ERα-mediated transcription of the gene. Earlier studies showed that brain ADCYAP1 transcript levels vary across the rat estrous cycle; with the greatest change occurring during proestrus [58], a period characterized by peak E 2 levels.…”
Section: Discussionsupporting
confidence: 93%
“…Our present study also demonstrates that this postsynaptic effect of PACAP in POMC neurons is sexually differentiated; with females being more sensitive than males in the presence of E 2 . This is consistent with the findings of Spence et al [57], in which expression of the Adcy-ap1r1 gene, encoding the PAC1 receptor, is upregulated in the nucleus accumbens of females compared to males, and enhanced by ERα-mediated transcription of the gene. Earlier studies showed that brain ADCYAP1 transcript levels vary across the rat estrous cycle; with the greatest change occurring during proestrus [58], a period characterized by peak E 2 levels.…”
Section: Discussionsupporting
confidence: 93%
“…In the females, ACE was associated with upregulation of the GABA A Receptor Epsilon Subunit, Gabre . In the context of substance use disorders, rats with a genetic predisposition to alcohol consumption showed a Gabre upregulation ( Spence et al, 2018 ). The hormone activity gene ontology was enriched in the female subset of DEGs, and, noteworthy, the neuropeptides included in this subset may be determining the dopaminergic activity in the NAcc shell of THC-treated females.…”
Section: Discussionmentioning
confidence: 99%
“…In the clinical literature, polymorphisms of the gene encoding the PACAP receptor, ADCYAP1R1 , have been associated with a diagnosis of posttraumatic stress disorder in women but not men, 37 and this association is particularly strong in women with low serum estradiol 38 . In preclinical studies, selectively bred alcohol‐preferring compared with nonpreferring female rats show upregulated expression in the NAc of Adcyap1r1 , and sequence variants in the promoter region for this gene are differentially responsive to stimulation by estrogen 39 . With this research suggesting that females overall may be more sensitive to the effects of PACAP, future work should fully characterize the effect of PACAP‐27 on ethanol consumption in this population, as females may show even greater benefit from PACAP treatment.…”
Section: Discussionmentioning
confidence: 99%